Penyuluhan Fisioterapi Komunitas tentang Frozen Shoulder Kepada Lansia di Pustu Kelurahan Buring, Kedungkandang - I Made Bagiada Okta Nugraha; Nurul Aini Rahmawati; Lisna Lisna (Lembaga Pengembangan Kinerja Dosen, 2024)
Elderly or old age is the final phase of the human life cycle, which is part of the natural life process that cannot be avoided by everyone. The elderly will experience degenerative diseases, one of which is musculoskeletal disease, namely frozen shoulder. Thus, there is a need to increase knowledge about frozen shoulder disease. The method provided in community physiotherapy activities is to provide education regarding the meaning, causes, risk factors, prevention, physiotherapy treatment and physiotherapy exercises using education media in the form of posters. In the question and answer discussion session, the elderly were very active in asking questions about the material presented by the students, because the elderly wanted to know about possible treatments and prevention. From the outreach activities that were carried out at the Buring Village Pustu, Kedungkandang, Malang City on October 25 2023, it can be concluded that it went smoothly and was well realized. The benefit of this outreach activity is to provide insight and knowledge regarding the prevention and treatment of stiff shoulder joints or frozen shoulder so that the knowledge of the elderly regarding frozen shoulder increases.